Mycobacterium lepromatosis as a Second Agent of Hansen’s Disease - Deps, Patrícia; Collin, Simon M. (Frontiers in Microbiology, 2021)
Mycobacterium lepromatosis was identified as a new species and second causal agent of Hansen’s disease (HD, or leprosy) in 2008, 150 years after the disease was first attributed to Mycobacterium leprae. M. lepromatosis has been implicated in a small number of HD cases, and clinical aspects of HD caused by M. lepromatosis are poorly characterized. HD is a recognized zoonosis through transmission of M. leprae from armadillos, but the role of M. lepromatosis as a zoonotic agent of HD is unknown. M. lepromatosis was initially associated with diffuse lepromatous leprosy, but subsequent case reports and surveys have linked it to other forms of HD. HD caused by M. lepromatosis has been reported from three endemic countries, Brazil, Myanmar, and Philippines, and three non-endemic countries, Mexico, Malaysia and USA. Contact with armadillos in Mexico was mentioned in 2/21 M. lepromatosis HD case reports since 2008. M. lepromatosis in animals has been investigated only in non-endemic countries, in squirrels and chipmunks in Europe, white-throated woodrats in Mexico, and armadillos in the USA. To date, there have only been a small number of positive findings in Eurasian red squirrels in Britain and Ireland. A single study of environmental samples found no M. lepromatosis in soil from a Scottish red squirrel habitat. Future studies must focus on endemic countries to determine the true proportion of HD cases caused by M. lepromatosis, and whether viable M. lepromatosis occurs in non-human sources.